Effects of Different Types of Task on Learners' Choice of Communication Strategies to Enhance Speaking Ability at a Malaysian Polytechnic - Kesavan, Prasanna (2011)
Second and foreign language learners often find themselves in circumstances where they have to express themselves in a target language. However, they usually lack the linguistics means to do so. These inadequacies or gaps may be in the form of a word, a phrase or a sentence. In such situations, some learners more often refrain from continuing their conversations while others normally rephrase their sentences in order for the interlocutor to understand them. These efforts are called oral communication strategies. The main aim of this study is to explore the effects of communicative task types on the students’ choice of communication strategies following strategy teaching in a Tourism Management classroom at a Malaysian polytechnic. It is envisaged that learners’ speaking ability would improve through this method. An intact class of 30 Diploma in Tourism Management students participated in this study. The research design employed in this study is quasi-experimental method using a time series design. In this design, repeated measures are taken before intervention and the scores are compared with the repeated measures taken after strategy teaching is carried out. Participants were taught four strategies (pauses, fillers and hesitations devices; appeal for assistance, circumlocution and approximation).Data were compiled Through self-report strategy use questionnaire, pre and post speaking tests and open-ended feedback questionnaire. Data were analysed through content analysis, t-test and multiple linear regression. The findings of this study reveal that learners of English in Tourism Management course have shown positive changes in their speaking ability. The selection and use of communicative strategies are closely related to the type of tasks that the participants have to perform. Pre and post results from self-report strategy use questionnaire revealed that the frequency of strategy use has increased after strategy teaching. Strategy teaching has also contributed towards enhancing these learners speaking ability based on the results from pre and post speaking tasks. Feedback questionnaire revealed that learners found using communicative strategies helped them to stay in interaction with their peers. The implications of the findings in this study are essential in planning the English language syllabus in Malaysian polytechnics and in developing classroom materials for second language learners